2019
DOI: 10.1002/eahr.500003
|View full text |Cite
|
Sign up to set email alerts
|

Local Knowledge and Single IRBs for Multisite Studies: Challenges and Solutions

Abstract: New federal policies require single IRB review for multisite studies, but many questions remain about how these IRBs will use local knowledge. The findings from our study, the first to examine how single IRBs perceive needs for local knowledge, reveal several challenges. Study respondents identified four potentially relevant types of local knowledge: about culture and linguistics, about geography and socioeconomics, about the researchers, and about the institutions. Such knowledge can potentially be obtained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Because the extent to which these goals are being achieved is unclear, we sought to enroll commercial (that is, for-profit) single IRBs and single IRBs at academic institutions and government agencies in an observational and interview study to assess challenges they face in implementing the new single IRB mandates. In previous publications, we reported findings about how single IRBs address issues about conflicts of interest, 3 local knowledge, 4 and reliance agreements. 5 Here we report findings about single IRBs' willingness or unwillingness to participate in research that investigates how they function.…”
mentioning
confidence: 99%
“…Because the extent to which these goals are being achieved is unclear, we sought to enroll commercial (that is, for-profit) single IRBs and single IRBs at academic institutions and government agencies in an observational and interview study to assess challenges they face in implementing the new single IRB mandates. In previous publications, we reported findings about how single IRBs address issues about conflicts of interest, 3 local knowledge, 4 and reliance agreements. 5 Here we report findings about single IRBs' willingness or unwillingness to participate in research that investigates how they function.…”
mentioning
confidence: 99%
“…At that time, stakeholders believed that the sIRB review process would lead to a lack of representation of the communities where the research would be conducted. Since then, research has shown that concerns about local knowledge may have been overstated 33 . Yet our findings show that stakeholders continue to be concerned and experience difficulties in considering local context.…”
Section: Discussionmentioning
confidence: 70%
“…34 SMART-IRB provides guidance on entering local context information and concerns in their online reliance agreement systems (SMART-IRB also has other tools to facilitate the sIRB review process). 35 Klitzman et al 36 suggest consideration of the following areas: linguistic and cultural issues, geographic and socioeconomic issues, researcherspecific issues, and institution-specific issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent empirical research conducted in the US also suggests that the importance of local knowledge can be overstated (but not necessarily irrelevant). 18 However, other empirical research I recently conducted also suggests that homogeneity (and in turn, greater consistency) of practice — and by corollary, trust by stakeholders in the processes and outcomes of a given ethics committee — depends crucially on two inter-related factors: 1) from a more top-down perspective, a robust overarching regulatory structure with committed leadership that works to improve procedural consistency across all ethics committees participating in a mutual recognition system; and 2) from a more bottom-up perspective, a stake-holder-led initiative with committed buy-in to drive change in the regulatory approach. Both a top-down and bottom-up approach are needed to effect robust and sustained regulatory change in ethics review.…”
Section: Introductionmentioning
confidence: 99%